2016
DOI: 10.1007/s00520-016-3195-1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in quality of life between American and Chinese breast cancer survivors

Abstract: Objective It has been speculated that cancer survivors in Asia may have lower quality of life (QOL) compared with their western counterparts. However, no studies made international comparisons in QOL using a comprehensive measure. This study aimed to compare Chinese breast cancer survivors’ QOL with United States (US) counterparts and examine if demographic and medical factors were associated with QOL across groups. Method The sample consisted of 159 breast cancer patients (97 Chinese and 62 US) who complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Regarding QOL, Chinese women reported statistically and clinically significantly lower QOL on the FACT-B total score as well as statistically significantly lower QOL on all sub-scales compared to US women (Table 2; details on these comparisons have been previously reported elsewhere [32]). In both samples, lower level of income was significantly associated with lower QOL ( p < 0.05).…”
Section: Resultsmentioning
confidence: 75%
“…Regarding QOL, Chinese women reported statistically and clinically significantly lower QOL on the FACT-B total score as well as statistically significantly lower QOL on all sub-scales compared to US women (Table 2; details on these comparisons have been previously reported elsewhere [32]). In both samples, lower level of income was significantly associated with lower QOL ( p < 0.05).…”
Section: Resultsmentioning
confidence: 75%
“…A study in Saudi Arabia showed breast cancer survivors reported a low overall global QoL, 29 whereas Chinese and U.S. breast cancer survivors reported poor QoL. 41 A study in Sweden reported poorer QoL in newly diagnosed breast cancer patients when compared with the normative population. 42 Our study suggested that employment was a negative predictor of role limitations due to emotional problems, vitality, and emotional well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Their results indicated that the HRQOL of their spouses is influenced by their own health status, anxiety/depression and relationship quality rather than the factors that relate to the people. Previous studies on other types of cancer in China and the United States have shown that the overall HRQOL of people with breast cancer in China is lower than that of people with breast cancer in the United States (Lu et al., ). Moreover, the low positive emotions of people with breast cancer in China have a greater influence on their emotional well‐being than do the low positive emotions of people with breast cancer in the United States (Milbury et al., ).…”
Section: Introductionmentioning
confidence: 96%
“…To date, however, few studies have analyzed the relationship between prostate cancer-specific anxiety and HRQOL in people and their spouses together. (Lu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%